The Development and Validation of the Dementia Quality of Life Scale for Older Family Carers (DQOL-OC) - Oliveira, D.C. (2017)
Background: Family carers are considered to be the most important resource available to support people with dementia. The number of older people who are carers is increasing in the United Kingdom, and little is known about how caregiving affects their quality of life (QoL). The World Health Organization has established the importance of measuring individuals’ QoL and of developing and using age-specific QoL tools. However, to date no dementia- and age-specific QoL scale has been developed for use with older family carers.